Effect of different curing methods on sewage sludge ash (SSA) concrete - Yee, Dar Luen (2016)
The increase of sewage sludge produced from waste water treatment plant is increasing worldwide. Disposal of sewage sludge is a serious issue as disposing them to landfill for decomposition is not a solution to solve this problem that endangers the environment. Thus, the aim of this research is to determine the effect of different curing methods on sewage sludge ash concrete in order to promote the use of sewage sludge ash in construction industry by partially replacing cement. The sewage sludge is incinerated at 800 degree Celsius at 3 hours 30 minutes. 10% cement replacement is used in this research as it is the optimum replacement percentage. Slump test, UPV test, Compressive test and Flexural test are carried out to determine the fresh concrete and hardened concrete properties. Results shows that SSA beam cured in salt water exhibits higher flexural strength that SSA beam cured in plain water. The compressive strength of both control and SSA cubes are higher initially but ultimately deteriorates. SSA cubes cured in salt water possess highest ultrasonic velocity among all SSA and control specimens on 90 days of curing. The findings suggested that curing SSA concrete in salt water is viable as it provides more advantage than disadvantage, which will lead to reduced usage of cement that solves the problem of sewage sludge disposal.